Pathways to prison: economic, personal, and relational motivations for drug offending in Indonesia - Hoyle, Carolyn (Capital drug laws in Asia, 2025)
Although there is a substantial body of research addressing the economic motivations for drug crime, fewer studies have also considered the social influences that shape individuals’ involvement in the illicit drug economy. This chapter will draw on interviews conducted in prisons in Indonesia with people convicted of drug offences. Analysis suggests that many offenders do have economic motivations for entry into the drug trade. However, personal and relational motivations for drug use and drug trading must not be ignored, given that most of our participants were not in absolute poverty when they decided to offend. Moreover, in making decisions about participation in the drug trade, they were clearly influenced by trusted peer groups. The chapter presents this empirical data within the context of increasingly punitive penalties for drug offences in Southeast Asia, including the judicial execution of drug traffickers.